Capturing the sequence of events during the water oxidation reaction in photosynthesis using XFELs. Issue 1 (15th November 2022) - Simon, Philipp S.; Makita, Hiroki; Bogacz, Isabel; Fuller, Franklin; Bhowmick, Asmit; Hussein, Rana; Ibrahim, Mohamed; Zhang, Miao; Chatterjee, Ruchira; Cheah, Mun Hon; Chernev, Petko; Doyle, Margaret D.; et al.
Abstract : Ever since the discovery that Mn was required for oxygen evolution in plants by Pirson in 1937 and the period‐four oscillation in flash‐induced oxygen evolution by Joliot and Kok in the 1970s, understanding of this process has advanced enormously using state‐of‐the‐art methods. The most recent in this series of innovative techniques was the introduction of X‐ray free‐electron lasers (XFELs) a decade ago, which led to another quantum leap in the understanding in this field, by enabling operando X‐ray structural and X‐ray spectroscopy studies at room temperature. This review summarizes the current understanding of the structure of Photosystem II (PS II) and its catalytic centre, the Mn4 CaO5 complex, in the intermediate S i ( i = 0–4)‐states of the Kok cycle, obtained using XFELs. Abstract : Water oxidation reaction in nature is catalysed by the Mn4 CaO5 cluster in Photosystem II. We have developed operando X‐ray crystallography and X‐ray spectroscopy methods at the X‐ray free‐electron laser facilities and applied them to understand the catalytic mechanism and associated protein dynamics in Photosystem II.